Strategi Guru Dalam Proses Belajar Mengajar Anak Dyspraxia - Khatimah, Husnul; Helmawati, Helmawati; Naqia, Naja; Hijriati, Hijriati (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study aims to analyze the strategies used by teachers in the teaching and learning process of children with dyspraxia in regular schools, as well as the challenges faced in accommodating children's special needs. The method used is qualitative research with a descriptive approach, involving observation and interviews with teachers at RA Takhrimah Tungkop, Aceh Besar. Data analysis used in this study used narrative analysis. The findings of the study indicate that teachers apply a holistic, adaptive, and collaborative approach, with learning differentiation strategies that include the use of visual aids and task simplification. Providing clear and gradual instructions, accompanied by repetition and direct guidance, has been shown to be effective in improving children's understanding and engagement. The results of this study recommend that teachers be given training on dyspraxia and inclusive classroom management, as well as providing supporting facilities to create a more conducive learning environment. With the implementation of the right strategies, it is hoped that children with dyspraxia can develop optimally and gain meaningful learning experiences in regular schools